Differential expression in RNA-seq: a matter of depth. - Tarazona, Sonia; García-Alcalde, Fernando; Dopazo, Joaquin; Ferrer, Alberto; Conesa, Ana (Genome Res, 2011)
Next-generation sequencing (NGS) technologies are revolutionizing genome research, and in particular, their application to transcriptomics (RNA-seq) is increasingly being used for gene expression profiling as a replacement for microarrays. However, the properties of RNA-seq data have not been yet fully established, and additional research is needed for understanding how these data respond to differential expression analysis. In this work, we set out to gain insights into the characteristics of RNA-seq data analysis by studying an important parameter of this technology: the sequencing depth. We have analyzed how sequencing depth affects the detection of transcripts and their identification as differentially expressed, looking at aspects such as transcript biotype, length, expression level, and fold-change. We have evaluated different algorithms available for the analysis of RNA-seq and proposed a novel approach--NOISeq--that differs from existing methods in that it is data-adaptive and nonparametric. Our results reveal that most existing methodologies suffer from a strong dependency on sequencing depth for their differential expression calls and that this results in a considerable number of false positives that increases as the number of reads grows. In contrast, our proposed method models the noise distribution from the actual data, can therefore better adapt to the size of the data set, and is more effective in controlling the rate of false discoveries. This work discusses the true potential of RNA-seq for studying regulation at low expression ranges, the noise within RNA-seq data, and the issue of replication.
Keywords: Algorithms; Expressed Sequence Tags; Gene Expression Profiling; Gene Expression Regulation; Humans; Models, Genetic; Oligonucleotide Array Sequence Analysis

Hypoxia promotes efficient differentiation of human embryonic stem cells to functional endothelium. - Prado-Lopez, Sonia; Conesa, Ana; Armiñán, Ana; Martínez-Losa, Magdalena; Escobedo-Lucea, Carmen; Gandia, Carolina; Tarazona, Sonia; Melguizo, Dario; Blesa, David; Montaner, David; Sanz-González, Silvia; Sepúlveda, Pilar; et al. (Stem Cells, 2010)
Early development of mammalian embryos occurs in an environment of relative hypoxia. Nevertheless, human embryonic stem cells (hESC), which are derived from the inner cell mass of blastocyst, are routinely cultured under the same atmospheric conditions (21% O(2)) as somatic cells. We hypothesized that O(2) levels modulate gene expression and differentiation potential of hESC, and thus, we performed gene profiling of hESC maintained under normoxic or hypoxic (1% or 5% O(2)) conditions. Our analysis revealed that hypoxia downregulates expression of pluripotency markers in hESC but increases significantly the expression of genes associated with angio- and vasculogenesis including vascular endothelial growth factor and angiopoitein-like proteins. Consequently, we were able to efficiently differentiate hESC to functional endothelial cells (EC) by varying O(2) levels; after 24 hours at 5% O(2), more than 50% of cells were CD34+. Transplantation of resulting endothelial-like cells improved both systolic function and fractional shortening in a rodent model of myocardial infarction. Moreover, analysis of the infarcted zone revealed that transplanted EC reduced the area of fibrous scar tissue by 50%. Thus, use of hypoxic conditions to specify the endothelial lineage suggests a novel strategy for cellular therapies aimed at repair of damaged vasculature in pathologies such as cerebral ischemia and myocardial infarction.
Keywords: Angiopoietin-1; Animals; biomarkers; Cell Culture Techniques; Cell Differentiation; Cell Hypoxia; Cell Transplantation; Cells, Cultured; Down-Regulation; Embryonic Stem Cells; Endothelial Cells; Gene Expression Profiling; Gene Expression Regulation; Humans; Male; Myocardial Infarction; Neovascularization, Physiologic; Oxygen; Pluripotent Stem Cells; Rats; Rats, Nude; Vascular Endothelial Growth Factor A